下面几个表达式不是多项式的有( )。
A: $x^{2}+2x+x^{\frac{1}{2}}-2$;
B: $\frac{x^{2}+1}{x+2}$;
C: $\frac{1}{2}$;
D: $x-\frac{1}{5}$.
A: $x^{2}+2x+x^{\frac{1}{2}}-2$;
B: $\frac{x^{2}+1}{x+2}$;
C: $\frac{1}{2}$;
D: $x-\frac{1}{5}$.
举一反三
- \(\int { { {\sec }^{3}}xdx}\)=( ) A: \(\frac{1}{2}\sec x\cot x-\frac{1}{2}\ln \left| \sec x+\tan x \right|+C\) B: \(\frac{1}{2}\sec x\tan x+\frac{1}{2}\ln \left| \sec x+\tan x \right|+C\) C: \(-\frac{1}{2}\csc x\tan x+\frac{1}{2}\ln \left| \sec x-\cot x \right|+C\) D: \(-\frac{1}{2}\sec x\tan x-\frac{1}{2}\ln \left| \csc x+\tan x \right|+C\)
- 微分方程$y' = \sqrt{x},y(1)=0$的解为 A: $ \frac{2}{3} x^{\frac{3}{2}} + C $ B: $ \frac{2}{3} x^{\frac{3}{2}} -\frac{2}{3} $ C: $ x^{\frac{3}{2}}-1 $ D: $ x^{\frac{3}{2}}+C $
- 微分方程\(2y''+5y'=5x^2-2x-1\)的通解是( )。 A: \(y=C_1+C_2e^{-\frac{5}{2}x}+\frac{1}{3}x^3-\frac{3}{5}x^2+\frac{7}{25}x\) B: \(y=C_1+C_2e^{-\frac{5}{2}x}+\frac{1}{3}x^3-\frac{3}{5}x^2\) C: \(y=C_1+C_2e^{-\frac{5}{2}x}+\frac{1}{3}x^3+\frac{7}{25}x\) D: \(y=C_1+C_2e^{-\frac{5}{2}x}-\frac{3}{5}x^2+\frac{7}{25}x\)
- 函数$f(x,y)={{\text{e}}^{-x}}\cos y$在点$(0,0)$处2次Taylor多项式为 A: $1+x+\frac{1}{2}({{x}^{2}}-{{y}^{2}})$ B: $1-x+\frac{1}{2}({{x}^{2}}-{{y}^{2}})$ C: $1-x+\frac{1}{2}({{x}^{2}}+{{y}^{2}})$ D: $1+x+\frac{1}{2}({{x}^{2}}+{{y}^{2}})$
- 方程${{x}^{2}}{{y}^{''}}-(x+2)(x{{y}^{'}}-y)={{x}^{4}}$的通解是( ) A: $y={{C}_{1}}x+{{C}_{2}}{{e}^{x}}-(\frac{1}{2}{{x}^{3}}+{{x}^{2}})$ B: $y={{C}_{1}}x+{{C}_{2}}{{e}^{x}}-(\frac{1}{2}{{x}^{3}}+{{x}^{4}})$ C: $y={{C}_{1}}x+{{C}_{2}}x{{e}^{x}}-(\frac{1}{2}{{x}^{3}}+{{x}^{4}})$ D: $y={{C}_{1}}x+{{C}_{2}}x{{e}^{x}}-(\frac{1}{2}{{x}^{3}}+{{x}^{2}})$